The Application Of Therapy For Drinking Boiled Cat's Whiskers Water To Reduce Uric Acid Levels, Which Is Applied Using Nola J. Pender's Theory In The Work Area Of The Jembatan Kecil Community Health Center, Bengkulu City - Marten, Aref; Murwati, Murwati (Utami Publisher, 2026)
The prevalence of gout among the elderly in Indonesia continues to increase. According to the 2018 Basic Health Research (Riskesdas), the prevalence of gout among the elderly based on a health professional’s diagnosis in Indonesia is 11.9%, and based on diagnosis or symptoms is 24.7%. When viewed based on age characteristics, the highest prevalence is found in individuals aged ≥ 75 years (54.8%). The purpose of this study is for the researcher to apply the therapy of consuming boiled cat’s whiskers (Orthosiphon aristatus) herbal drink to reduce uric acid levels, implemented using Nola J. Pender’s Health Promotion Theory in the Working Area of Jembatan Kecil Public Health Center, Bengkulu City, in 2025.The research method used in this study is a case study approach by applying boiled cat’s whiskers water therapy to decrease uric acid levels through the application of Nola J. Pender’s theory. The number of participants in this study was two individuals with similar conditions, namely nursing problems of acute pain related to physiological injury agents and lack of knowledge related to inability to recognize the disease condition.The results showed that the application of the therapy was highly effective in reducing uric acid levels in patients with hypertension through the application of Nola J. Pender’s theory in the Working Area of Jembatan Kecil Public Health Center, Bengkulu City, in 2025.The researcher recommends that patients and families continue to maintain physical, psychological, and environmental health, and consistently follow the advice provided, apply, and implement all knowledge taught to help patients and families achieve an optimal level of health.